2012
DOI: 10.1007/s10616-012-9465-y
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in genes expression patterns during in vitro differentiation of mouse spermatogonial cells into neuroepithelial-like cells

Abstract: Pluripotent stem cells derived from testis is a new, natural, and unlimited source for cell therapy in regenerative medicine and represent a possible alternative to replacing of all cells in the body. Here, we designed a simple co-culture system of spermatogonia cells with Sertoli cells for the generation of embryonic stem-like cells from mouse testis. The importance of our simple method will be clear when we compared it with other complex and time-consuming methods. Embryonic stem-like colonies with sharp bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
(23 reference statements)
1
9
0
Order By: Relevance
“…In fact Oct4 has been shown to function as core transcription factor in maintain self-renewal of embryonic stem cells and SSCs. This data is similar to previous results that reported the differentiation of SSCs into different lineage specifically neural precursor under the define culture conditions (13,15,(32)(33). Mizrak et al mentioned that culture conditions support the differentiation of SSCs (14).…”
Section: Discussionsupporting
confidence: 92%
“…In fact Oct4 has been shown to function as core transcription factor in maintain self-renewal of embryonic stem cells and SSCs. This data is similar to previous results that reported the differentiation of SSCs into different lineage specifically neural precursor under the define culture conditions (13,15,(32)(33). Mizrak et al mentioned that culture conditions support the differentiation of SSCs (14).…”
Section: Discussionsupporting
confidence: 92%
“…Similar to previous reports these inducers can improve the neural differentiation in pluripotent stem cells population include: ES and ES Like cells. 18,19,23 Our date indicated that cells grown on Silk scaffold were significantly higher than monolayer cell group. Evaluation of cell culture seeded in silk scaffold confirmed that nanofibers structures can regulate cellular adherence, viability and proliferation.…”
Section: Discussionmentioning
confidence: 83%
“…Improved expression of mature neuron markers: Map2 and ß tubulin shows the functional promoting role of theses regents in neural maturation. Similar to previous reports these inducers can improve the neural differentiation in pluripotent stem cells population include: ES and ES Like cells …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations